Cell-type specific effects of mineralocorticoid receptor gene expression suggest intercellular communication regulating fibrosis in skeletal muscle disease - Gomatam, Chetan K.; Ingale, Pratham; Rodriguez, Gabriel; Munger, Sarah; Pomeranets, Rachel; Krishna, Swathy; Lowe, Jeovanna; Howard, Zachary M.; Rafael-Fortney, Jill A. (Frontiers in Physiology, 2024)
Duchenne muscular dystrophy (DMD) is a fatal striated muscle degenerative disease. DMD is caused by loss of dystrophin protein, which results in sarcolemmal instability and cycles of myofiber degeneration and regeneration. Pathology is exacerbated by overactivation of infiltrating immune cells and fibroblasts, which leads to chronic inflammation and fibrosis.Mineralocorticoid receptors (MR), a type of nuclear steroid hormone receptor, are potentialWe show for the first time that conditional knockout of mineralocorticoid receptors (MR) in myofibers and myeloid cells have contrasting effects on gene expression in the dystrophic skeletal muscle microenvironment. Inhibition of MR signaling with MR antagonists has previously shown clinical efficacy in Duchenne muscular dystrophy (DMD) cardiomyopathy and preclinical efficacy in skeletal muscle in DMD models. Myeloid MR knockout led to increases in myofibroblast gene expression, supporting MR-regulated crosstalk between inflammatory cells and fibroblasts. Surprisingly, lysyl oxidase (Lox), canonically a collagen crosslinker, was increased in both myofiber and myeloid MR knockouts, but did not localize to fibrotic regions of dystrophic skeletal muscle. Lox localized within myofibers, including only a region of quadriceps muscles. Lysyl oxidase like 1 (Loxl1), another Lox family member, was increased only in myeloid MR knockout muscle and Loxl1 localized specifically to fibrotic regions, supporting Loxl1 as a new anti-fibrotic target in muscle. Both myofiber and myeloid MR knockout changed expression of genes involved in inflammation. Fibrosis and inflammation exacerbate pathology of muscular dystrophies, so defining signals between cell-types in the striated muscle microenvironment will ultimately be required for optimal therapeutic approaches for muscle diseases.